IMMU-12. PHASE I/II TRIAL OF IMMUNOTHERAPY WITH FUSIONS OF DENDRITIC CELLS AND TUMOR CELLS FOR RELAPSED OR REFRACTORY BRAIN TUMORS IN CHILDREN AND YOUNG ADULTS. (4th December 2020) - Yamaoka, Masayoshi; Akasaki, Yasuharu; Takei, Jun; Akiyama, Masaharu; Tasaki, Tetsunori; Ohashi, Toya; Ida, Hiroyuki; Yanagisawa, Takaaki
Abstract: BACKGROUND/OBJECTIVES: Relapsed or refractory brain tumors in childhood continue to have a dismal prognosis in spite of intensive multidisciplinary treatment. Cancer immunotherapy is newly developed to be expected as next promising treatment for highly aggressive pediatric cancer. This trial was designed to evaluate the safety and effectiveness of an immunotherapy with fusions of dendritic cells (DCs) and tumor cells in patients with malignant brain tumors. METHODS: Patients with histopathologically confirmed malignant and recurrent/refractory brain tumor were eligible for this immunotherapy trial. Autologous cultured tumor cells obtained from surgical specimens were fused with autologous DCs using polyethylene glycol. The fusion cells (FC) were inoculated intradermally in the cervical region and repeated 3–10 times in each 28–84 days cycle. Treatment-related toxicity, progression-free survival (PFS), and overall survival (OS) were evaluated. RESULTS: Six patients were enrolled, three with high grade glioma and three with ependymoma. Median age at first course of immunotherapy was 10 years (range 8–25 years) and median follow-up time from the first course of immunotherapy was 13.5 months (range 3–33 months). All patients with immunotherapy were well tolerated to this treatment with no adverse events except local erythema in injected site. Median progression free survival and overall survival were 18 months and 18.5 months, respectively. CONCLUSIONS: FC immunotherapy with autologous DCs and tumor cells for brain tumor in children and young adults were extremely well tolerated and showed encouraging responses in this series. Further phase II study of FC immunotherapy is planned to improve survival and reduce treatment related morbidity.